TRAF6 is a critical mediator of signal transduction by the viral oncogene latent membrane protein 1 - Schultheiss, Ute (Oxford University Press, 2001)
The oncogenic latent membrane protein 1 (LMP1) of the Epstein–Barr virus recruits tumor necrosis factor-receptor (TNFR)-associated factors (TRAFs), the TNFR-associated death domain protein (TRADD) and JAK3 to induce intracellular signaling pathways. LMP1 serves as the prototype of a TRADD-binding receptor that transforms cells but does not induce apoptosis. Here we show that TRAF6 critically mediates LMP1 signaling to p38 mitogen-activated protein kinase (MAPK) via a MAPK kinase 6-dependent pathway. In addition, NF-κB but not c-Jun N-terminal kinase 1 (JNK1) induction by LMP1 involves TRAF6. The PxQxT motif of the LMP1 C-terminal activator region 1 (CTAR1) and tyrosine 384 of CTAR2 together are essential for full p38 MAPK activation and for TRAF6 recruitment to the LMP1 signaling complex. Dominant-negative TRADD blocks p38 MAPK activation by LMP1. The data suggest that entry of TRAF6 into the LMP1 complex is mediated by TRADD and TRAF2. In TRAF6-knockout fibroblasts, significant induction of p38 MAPK by LMP1 is dependent on the ectopic expression of TRAF6. We describe a novel role of TRAF6 as an essential signaling mediator of a transforming oncogene, downstream of TRADD and TRAF2.